How should the distant future be discounted when discount rates are uncertain? - Christian Gollier; Martin L. Weitzman (Center for Economic Studies and ifo Institute (CESifo), 2009)
It is not immediately clear how to discount distant-future events, like climate change, when the distant-future discount rate itself is uncertain. The so-called Weitzman-Gollier puzzle is the fact that two seemingly symmetric and equally plausible ways of dealing with uncertain future discount rates appear to give diametrically opposed results with the opposite policy implications. We explain how the Weitzman-Gollier puzzle is resolved. When agents optimize their consumption plans and probabilities are adjusted for risk, the two approaches are identical. What we would wish a reader to take away from this paper is the bottom-line message that the appropriate long run discount rate declines over time toward its lowest possible value.
Keywords: G12; E43; Q51; 330; discount rate; term structure; climate change; cost-benefit analysis; Soziale Diskontrate; Abzinsung; Zinsstruktur; Klimaveränderung; Klimaschutz; Kosten-Nutzen-Analyse; Theorie